A proposal to avoid leakage of CO2 from onboard high-pressure CO2 cylinders. Issue 3 (2nd July 2020) - Lee, Kyoung-Woo; Yun, Jeong-in; Lee, Won-Ju; Rho, Beom-Seok; Cho, Jang-Won; Choi, Jae-Hyuk
ABSTRACT: The CO2 system is the most widely used fire extinguishing system in ships and proper maintenance should be carried out to prevent CO2 leakage, malfunction to human safety, and maintain fire extinguishing capability. IMO has published MSC.1/Circ.1318 as a guideline for the maintenance of the CO2 system. However, various problems were found in MSC.1/Circ.1318, such as unclear guidelines for hydrostatic testing of CO2 cylinders. in this study, to prevent CO2 leakage and malfunction in the CO2 system, the reason for the problems identified in MSC.1/Circ.1318 was reviewed and alternatives were proposed.